(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
The construction of highways includes stylistic works consisting of certain processes, namely the road base, road bed and Su’niy structures. The technology of road construction work is aimed at materials, semi-finished products, the preparation of fragments and parts of road structures, ensuring quality indicators in the dam. It is necessary to plan the implementation of the processes of road curving in a wide-scale mechanization-assisted and automated way.